2022
DOI: 10.3389/fneur.2022.772333
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Therapy for Infantile Spasms: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThe limitations of adrenocorticotrophic hormone (ACTH) treatment for infantile spasms (ISs), such as high costs, limited availability, and adverse effects (AEs), make it necessary to explore whether corticosteroids are optimal alternatives. Many other compelling treatments have gone through trials due to the suboptimal effectiveness of hormonal therapy. A systematic review and meta-analysis were performed to evaluate the effectiveness and safety of hormonal therapy for patients with ISs.MethodsEMBASE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 34 publications
0
12
0
3
Order By: Relevance
“…The reoccurrence of seizures after a period of seizure freedom was extracted, if possible, from the studies. Because structured meta-analysis for epileptic spasms exists, no analysis was performed on this cohort (5,6). The PRISMA flowchart is shown in Supplementary Figure 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reoccurrence of seizures after a period of seizure freedom was extracted, if possible, from the studies. Because structured meta-analysis for epileptic spasms exists, no analysis was performed on this cohort (5,6). The PRISMA flowchart is shown in Supplementary Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In 1958, Sorel and Dusaucy-Bauloye first reported a marked improvement in 21 patients with epileptic spasms treated with ACTH (4). Since then, corticosteroids have evolved into an essential component of the standard therapy of epileptic spasms backed up by evidence of randomized controlled trials (RCTs) (5,6). Nevertheless, for other childhood epilepsies, various treatment algorithms exist that encompass several steroids including prednisolone, adrenocorticotrophin hormone (ACTH), methylprednisolone, hydrocortisone, and the novel neurosteroid ganaxolone as well as a multifold of protocols .…”
Section: Introductionmentioning
confidence: 99%
“…Although the relevance between the SIK1 mutation and autistic behaviors has been uncovered in SIK1-MT mice, the effect of the SIK1 mutation on epilepsy remains enigmatic. In addition, considering the role of SIK1 in ACTH signaling, it would be intriguing to investigate the effect of ACTH on SIK1-MT mice because ACTH is the first-line drug for infantile spasms [ 16 , 17 , 18 ]. In the present study, we investigated the effect of the C-terminal truncated mutation of SIK1 on epilepsy by inducing seizures in SIK1-MT mice.…”
Section: Introductionmentioning
confidence: 99%
“…PKA phosphorylates a serine at position 577 (S577) of SIK1 [6,7]. Phosphorylated SIK1 upregulates the cAMP response element binding (CREB) protein 2 of 16 and downregulates the myocyte enhancer factor 2 (MEF2) functions by phosphorylating cAMP-regulated transcriptional co-activators (CRTC) and the class IIa histone deacetylases (HDAC), respectively [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses demonstrated that the efficacy of high-dose oral prednisolone is comparable to ACTH for the electro-clinical remission of infantile spasms in WS. [ 3 4 ] In addition, low-dose ACTH was found to have comparable effectiveness but a lower incidence of adverse effects. Thus, high-dose oral prednisolone is currently widely used as the first-choice medication for the treatment of WS as the short-, medium-, and long-term seizure, and development outcomes have been found to be similar compared to ACTH.…”
mentioning
confidence: 99%